Women’s vulnerability to climatic and non-climatic change in the Eastern Gangetic Plains - International Water Management Institute (International Water Management Institute, 2014)
Climate change poses critical challenges for farmers across South Asia, and vulnerability often takes on a gendered dimension. Findings from IWMI’s research conducted in Madhubani, Bihar, India, and in Dhanusha and Morang of the Nepal Terai (Madhesh) substantiate previous literature on the region by showing how men and women are differentially affected by climate change. However, another set of findings, outlined in this policy brief, show how gendered vulnerability stems from a diverse set of climatic and non-climatic causes, and is not always direct, and policy responses should be tailored accordingly.